2021
DOI: 10.1016/j.gendis.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-resistance and depression cohort data mining to identify nutraceutical related DNA methylation biomarker for type 2 diabetes

Abstract: Insulin-resistance (IR) is one of the most important precursors of type 2 diabetes (T2D). Recent evidence suggests an association of depression with the onset of T2D. Accumulating evidence shows that depression and T2D share common biological origins, and DNA methylation examination might reveal the link between lifestyle, disease risk, and potential therapeutic targets for T2D. Here we hypothesize that integrative mining of IR and depression cohort data will facilitate predictive biomarkers identification for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…On the other hand, our research group previously applied the SIMPO algorithm to the prediction of disease-related biomarkers. As a result, these studies successfully identified several DNA methylation biomarkers related to the onset of type 2 diabetes and colorectal cancer and were supported by clinical trials ( Quan et al, 2020a ; Liang et al, 2020 ). In summary, SIMPO-TSS1500 algorithm has good robustness and biological significance.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, our research group previously applied the SIMPO algorithm to the prediction of disease-related biomarkers. As a result, these studies successfully identified several DNA methylation biomarkers related to the onset of type 2 diabetes and colorectal cancer and were supported by clinical trials ( Quan et al, 2020a ; Liang et al, 2020 ). In summary, SIMPO-TSS1500 algorithm has good robustness and biological significance.…”
Section: Discussionmentioning
confidence: 79%
“…Cloud Computing Platform. Cloud computing platforms can be divided into three categories: cloud storage platforms that focus on data storage, cloud computing platforms that focus on data processing, and comprehensive cloud computing platforms that take into account both computing and data storage and processing [13,14]. As a leading cloud service provider in China, Alibaba Cloud has high stability and practicability and has been widely recognized by users.…”
Section: Data Mining Algorithm Model Constructionmentioning
confidence: 99%
“…Por estos esfuerzos, es posible que la bioinformática se pueda aplicar en diversos campos. A menudo es posible utilizar estas técnicas para la identificación de ciertos genes y secuencias base, así como la correlación entre ellos para de este modo poder descubrir la cura para enfermedades (Gingeras et al, 1998;Wilson et al, 2018;Liang et al, 2020;Kwon et al, 2020). No obstante, aún existen muchas desventajas del uso de la bioinformática, principalmente por la cantidad de información genómica disponible, la cual es enorme y por lo tanto el tiempo para analizarla también se vuelve considerable.…”
Section: Descripción Del Métodounclassified